The evolution of intermodal transport research and its development issues - Jaržemskienė, Ilona (Transport, 2007)
Scientific papers related to intermodal transport research are reviewed in the article. Attention is focused on classification of scientific issues of intermodality. The methods, algorithms, models used for intermodal transport research are described. The areas of huge scientific focus and poor areas in intermodality research are highlighted. First Published Online: 27 Oct 2010